2013
DOI: 10.1097/pap.0b013e318286245d
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioblastoma-like Clear Cell Stromal Tumor of the Lung

Abstract: The authors report 2 cases of an apparently unpublished stromal tumor of the lung characterized by a predominantly endobronchial growth pattern and benign-appearing clear cells. Both tumors were discovered incidentally in adult patients during routine workups for other medical reasons and treated with lobectomy. On gross inspection there was no evidence of infiltration of the adjacent lung tissue. Microscopically, both lesions featured monotonous oval-shaped to spindle-shaped cells growing in a vaguely nested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 7 publications
5
18
0
Order By: Relevance
“…All but two of the reported cases showed minimal cytological atypia, no nuclear pleomorphism and no mitotic activity. 1,2,12 The two pulmonary cases reported in the current study showed similar morphological features, although clear cells appeared to be only a minor component in our cases. Specifically, in case 2, we were unable to find any areas that shows definitive cytoplasmic clearing.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…All but two of the reported cases showed minimal cytological atypia, no nuclear pleomorphism and no mitotic activity. 1,2,12 The two pulmonary cases reported in the current study showed similar morphological features, although clear cells appeared to be only a minor component in our cases. Specifically, in case 2, we were unable to find any areas that shows definitive cytoplasmic clearing.…”
Section: Discussionsupporting
confidence: 76%
“…These tumours were characterised by a hypervascularised stroma and dilated blood vessels, hence the original name ‘haemangioblastoma‐like clear cell stromal tumour of the lung’. All but two of the reported cases showed minimal cytological atypia, no nuclear pleomorphism and no mitotic activity 1,2,12 . The two pulmonary cases reported in the current study showed similar morphological features, although clear cells appeared to be only a minor component in our cases.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, they may be rarely found in the retroperitoneum, pelvic cavity, presacral region, kidney, maxillary sinus, and adrenal gland ( 4 ). In 2013, Falconieri et al ( 5 ) reported the first two cases of pulmonary clear cell stromal tumors with previously unreported histological features similar to hemangioblastoma, which they named “hemangioblastoma-like clear cell stromal tumor of the lung”. The HLCCST is very uncommon, to the best of the authors’ knowledge, only 13 cases have been reported in four articles.…”
Section: Discussionmentioning
confidence: 99%
“…8 Overall, the present histological and immunoprofiling features do not support the diagnosis of hyalinizing CCC. Hemangioblastoma-like clear cell tumor (HLCCST) of the lung, recently designated by two independent publications, 12,13 is also one of the differential diagnoses. Although rich and fine capillary networks typically shown in HLCCST of the lung are not found in the present case, further molecular testing of the previously reported cases 12,13 are required.…”
Section: Discussionmentioning
confidence: 99%